Poland’s national and EU agricultural budget after 2015. Reduction in expenditures and directions of change - Czyżewski Andrzej; Matuszczak Anna (Management, 2019)
The aim of the article was to present changes which took place in the financing of the agricultural sector in Poland after 2015, i.e. from the moment when a new economic option started to emerge in the national economic policy. A transition from the pro-liberal to the pro-social option is noticeable, which is reflected in the restrictions on expenditures in the national agricultural budget. Similar trends can be observed in the expenditures from the European funds budget, which are also increasingly lower. Symptoms of the renationalisation of the agricultural budget can also be observed, consisting in an initial increase in national expenditures and a relative decrease in the expenditures from the European funds budget, but to a different extent in the years under study. The article analyses the level, then the share of expenditures on the agricultural sector in the budget altogether and in GDP, taking into consideration both the expenditures on the Agricultural Social Insurance Fund (ASIF) and funds from the EU budget. Next, it concentrates more closely on relations in the financing of domestic agriculture from national and EU funds, and finally, points to the social issues related to the agricultural sector through the prism of expenditures on ASIF.